Do Hostile Media Perceptions Lead to Action? The Role of Hostile Media Perceptions, Political Efficacy, and Ideology in Predicting Climate Change Activism. (December 2017) - Feldman, Lauren; Hart, P. Sol; Leiserowitz, Anthony; Maibach, Edward; Roser-Renouf, Connie
This study joins a growing body of research that demonstrates the behavioral consequences of hostile media perceptions. Using survey data from a nationally representative U.S. sample, this study tests a moderated-mediation model examining the direct and indirect effects of hostile media perceptions on climate change activism. The model includes external political efficacy as a mediator and political ideology and internal political efficacy as moderators. The results show that hostile media perceptions have a direct association with climate activism that is conditioned by political ideology: Among liberals, hostile media perceptions promote activism, whereas among conservatives, they decrease activism. Hostile media perceptions also have a negative, indirect relationship with activism that is mediated through external political efficacy; however, this relationship is conditioned by both ideology and internal political efficacy. Specifically, the indirect effect manifests exclusively among conservatives and moderates who have low internal efficacy. Theoretical, normative, and practical implications are discussed.